Safety and Pharmacokinetics of Glecaprevir/Pibrentasvir in Adults With Chronic Genotype 1–6 Hepatitis C Virus Infections and Compensated Liver Disease. (28th March 2019) - Gane, Edward; Poordad, Fred; Zadeikis, Neddie; Valdes, Joaquin; Lin, Chih-Wei; Liu, Wei; Asatryan, Armen; Wang, Stanley; Stedman, Catherine; Greenbloom, Susan; Nguyen, Tuan; Elkhashab, Magdy; et al.
Abstract: Background: Untreated, chronic hepatitis C virus (HCV) infection may lead to progressive liver damage, which can be mitigated by successful treatment. This integrated analysis reports the safety, efficacy, and pharmacokinetics (PK) of the ribavirin-free, direct-acting, antiviral, fixed-dose combination of glecaprevir/pibrentasvir (G/P) in patients with chronic HCV genotype 1–6 infections and compensated liver disease, including patients with chronic kidney disease stages 4 or 5 (CKD 4/5). Methods: Data from 9 Phase II and III clinical trials, assessing the efficacy and safety of G/P treatment for 8–16 weeks, were included. The presence of cirrhosis was determined at screening using a liver biopsy, transient elastography, or serum biomarkers. The objectives were to evaluate safety, the rate of sustained virologic response at post-treatment week 12 (SVR12 ), and steady-state PK by cirrhosis status. Results: Among 2369 patients, 308 (13%) were Child-Pugh Class A, including 20 with CKD 4/5. Overall, <1% of patients experienced an adverse event (AE) that led to G/P discontinuation or G/P-related serious AEs (SAEs). The most common AEs were headache and fatigue, occurring at similar frequencies with and without cirrhosis. SAEs were more common in patients with CKD 4/5, but all were unrelated to G/P. There were no cases of drug-induced liver injury or clinically relevant hepatic decompensation. SVR12 rates were 96.4% (297/308) with compensated cirrhosis and 97.5% (2010/2061) without cirrhosis. PK analysis demonstrated a 2.2-fold increase in glecaprevir exposure, but not pibrentasvir exposure, in patients with compensated cirrhosis. Conclusions: G/P was safe and efficacious in patients with compensated liver disease, including those with CKD 4/5. Clinical Trials Registration: NCT02243280, NCT02243293, NCT02604017, NCT02640482, NCT02640157, NCT02636595, NCT02642432, NCT02651194, and NCT02446717 Abstract : Glecaprevir/pibrentasvir is a safe and efficacious pangenotypic, direct-acting antiviral regimen for hepatitis C virus patients with Child-Pugh A cirrhosis (including with chronic kidney disease stages 4 or 5), despite a 2-fold increase in glecaprevir exposures in patients with compensated cirrhosis.